The Effect of Selling Prices and Discounts on Purchasing Power and Customer Loyalty (Marketing Management Review Literature) - Hamdani, Mohammad (Dinasti International Journal of Digital Business Management, 2022)
The Literature Review article on the Effect of Selling Prices and Discounts on Purchasing Power and Customer Loyalty is a scientific article that has the aim of building a research hypothesis on the influence between variables that will be used in subsequent research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media including Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Selling Price has an effect on Purchasing Power; 2) Discounts have an effect on Purchasing Power; 3) Selling Price affects Customer Loyalty; 4) Discounts affect Customer Loyalty; and 5) Purchasing Power affects Customer Loyalty. Apart from these 2 exogenous variables that affect the endogenous variables of Purchasing Power and Customer Loyalty, there are many other factors, including product availability, income, customer satisfaction, and location variables.